OPTIMIZATION MODELS AND FORECASTS FOR EFFECTIVE MANAGEMENT OF INVESTMENT PORTFOLIOS (Innovate Conferences, 2026)
Today, one of the most important concerns of investment and financial managers is making prompt and optimal decisions in the presence of large volumes of data and information related to stock and capital markets. In particular, as the level of diversification within investment portfolios increases, it becomes critically important to make sound decisions while taking into account constraints related to expected returns, asset risk levels, liquidity, and other variables.